LncRNA FOXD3-AS1 Promotes the Malignant Progression of Nasopharyngeal Carcinoma Through Enhancing the Transcription of YBX1 by H3K27Ac Modification - Yang, Huiyun; Pan, Yuliang; Zhang, Jun; Jin, Long; Zhang, Xi (Frontiers in Oncology, 2021)
Background:Long noncoding RNAs (lncRNAs) can effect the progression of various tumors, including nasopharyngeal carcinoma (NPC). Here, lncRNA FOXD3-AS1 is highly expressed in NPC tissues through bioinformatics analysis and related to the malignant progression of NPC. Methods:Bioinformatics analysis and real-time reverse transcription quantitative PCR(RT-qPCR) assay were applied to identiify the expression of FOXD3-AS1 in NPC tissues and cells. Specific short hairpin RNAs(shRNAs) or overexpression plasmids were used to knockdown or upregulate FOXD3-AS1 in NPC cells. The effect of FOXD3-AS1 on proliferation and metastasis of NPC was confirmed by CCK8, colony formation, transwell assays in vitro and mouse tumor growth and metastasis models in vivo, of which the mechanism was explored by RNA pull down,mass spectrometry (MS), RNA Immunoprecipitation(RIP), chromatin immunoprecipitation (CHIP) and luciferase assays. Results:FOXD3-AS1 was highly expressed in NPC tissues and cells. Knockdown of FOXD3-AS1 significantly inhibited proliferation, migration and invasion of NPC cells in vitro and vivo. FOXD3-AS1 could specifically bind to YBX1, and have an negative effect on the expression of YBX1. Bioinformatics analysis showed that the promoter of YBX1 had a high enrichment of H3K27ac,which promote mRNA transcription and protein translation of YBX1. Moreover, overexpression of YBX1 could reverse the proliferation, migration and invasion arrest caused by FOXD3-AS1 knockdown. Conclusion:LncRNA FOXD3-AS1 is highly expressed and promotes malignant phenotype in NPC, which may provide a new molecular mechanism for NPC.